2003
DOI: 10.1242/jcs.00693
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3 regulates formation of long lamellipodia in human keratinocytes

Abstract: During wound healing, keratinocytes initiate migration from the wound edge by extending lamellipodia into a fibronectin-rich provisional matrix. While lamellipodia-like structures are also found in cultured keratinocytes exposed to epidermal growth factor (EGF), the signaling pathway that regulates the formation of these structures is not defined. In cultured human keratinocytes seeded on fibronectin, we found that protein-serine/threonine kinase inhibitors including staurosporine, induced concentration-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 66 publications
3
60
0
Order By: Relevance
“…3B) and number of tracks (Fig. 3C) Inactivation of GSK-3β mimics JAM-A-dependent inhibition of motility Similarly to the expression of JAM-A in our system, inactivation of GSK-3β was shown to reduce long protrusions in keratinocytes (Koivisto et al, 2003). Thus, we surmised that JAM-A expression might inhibit protrusions (and possibly motility) by inactivating GSK-3β.…”
Section: Jam-a Expression In Endothelial Cellssupporting
confidence: 63%
See 1 more Smart Citation
“…3B) and number of tracks (Fig. 3C) Inactivation of GSK-3β mimics JAM-A-dependent inhibition of motility Similarly to the expression of JAM-A in our system, inactivation of GSK-3β was shown to reduce long protrusions in keratinocytes (Koivisto et al, 2003). Thus, we surmised that JAM-A expression might inhibit protrusions (and possibly motility) by inactivating GSK-3β.…”
Section: Jam-a Expression In Endothelial Cellssupporting
confidence: 63%
“…First, GSK-3β inhibitors prevent the formation of long lamellipodia in keratinocytes (Koivisto et al, 2003) and filopodia in neurons (Owen and Gordon-Weeks, 1999). In addition, inactive GSK-3β localizes to the leading edge of growth cones (Eickholt et al, 2002).…”
Section: Jam-a and The Pkcζ/gsk-3β Axismentioning
confidence: 99%
“…Arf6 is also involved in vesicle trafficking, membrane ruffling, as well as lamellipodia formation (Turner & Brown, 2001). It has been shown that GSK3 activity is required for keratinocytes to form lamellipodia and migrate directionally in response to wound signaling (Koivisto et al, 2003). Similarly, GSK3 activates Rac in response to wound signaling in intestinal epithelial cells.…”
Section: Migrationmentioning
confidence: 99%
“…GSK-3 has also been shown to be involved in signaling activated by cell adhesion in nonneuronal cells (23,37). The formation of extending lamellipodia in migrating keratinocytes is blocked by GSK-3 inhibitors (29). The initiation and stimulation of sperm motility are accompanied by the inactivation of GSK-3 (41).…”
mentioning
confidence: 99%